Transnational news media coverage of distant suffering in the Syrian civil war: An analysis of CNN, Al-Jazeera English and Sputnik online news. (December 2020) - Zhang, Xu; Luther, Catherine A.
This study analyzed news stories published on the online sites of CNN, Al-Jazeera English, and Sputnik to investigate how the transnational news outlets framed the human suffering associated with the Syrian war. Unlike prior studies that have tended to be based on traditional nation-state paradigms, this research approached the analysis from a cosmopolitan perspective. The findings revealed that in concert with standard journalistic routines and news values, all three news outlets commonly employed a mass death and displacement frame to depict human suffering inside Syria. The adoption of this frame suggests that in telling the story of human suffering, the three media outlets focused on brief facts and shocking statistics without detailed depictions of the human suffering. The meager presence of a cosmopolitan outlook in the news coverage indicates that although transnational media target a global audience with English as Lingua Franca, they cannot be completely independent of geopolitics.